A CORRELATIONAL STUDY OF LANGUAGE LEARNING STRATEGIES AND ENGLISH PROFICIENCY OF UNIVERSITY STUDENTS AT EFL CONTEXT - Sindi Anggarista; Achmad Yudi Wahyudin (Faculty of Arts and Education, 2022)
Mastering English requires the students to have their own strategy. The use of appropriate language learning strategies may help the students to be proficient in English. This research investigates the language learning strategies used by EFL students and their relationship with the Students’ English Proficiency. This study adopted Ex-post facto quantitative research design in which the data were collected from the result of students Language Learning Inventory and also the data of their latest English Proficiency Score. 38 students majoring in English participated in this research. The result of this research shows that metacognitive strategies were the most frequent strategy, followed by cognitive strategy, compensation strategy, memory strategy, affective strategy, and social strategies. Additionally, there is a significant correlation between language learning strategy use and students’ English proficiency.